F-Box Protein FBXW17-Mediated Proteasomal Degradation of Protein Methyltransferase PRMT6 Exaggerates CSE-Induced Lung Epithelial Inflammation and Apoptosis - Li, Tiao; He, Xue; Luo, Lijuan; Zeng, Huihui; Ren, Siying; Chen, Yan (Frontiers in Cell and Developmental Biology, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic debilitating lung disease, characterized by progressive airway inflammation and lung structural cell death. Cigarette smoke is considered the most common risk factor of COPD pathogenesis. Understanding the molecular mechanisms of persistent inflammation and epithelial apoptosis induced by cigarette smoke would be extremely beneficial for improving the treatment and prevention of COPD. A histone methyl modifier, PRMT6, is reported to alleviate CSE-induced emphysema through inhibiting inflammation and cell apoptosis. However, few studies have focused on the modulation of PRMT6 in regulating inflammation and cell apoptosis. In this study, we showed that protein expression of PRMT6 was aberrantly decreased in the lung tissue of COPD patients and cigarette smoke extract (CSE)-treated epithelial cells. FBXW17, a member of the Skp1‒Cullin‒F-box (SCF) family of E3 ubiquitin ligases, selectively bound to PRMT6 in nuclei to modulate its elimination in the proteasome system. Proteasome inhibitor or silencing of FBXW17 abrogated CSE-induced PRMT6 protein degradation. Furthermore, negative alteration of FBXW17/PRMT6 signaling lessened the pro-apoptotic and pro-inflammatory effects of CSE in lung epithelial cells. Our study, therefore, provides a potential therapeutic target against the airway inflammation and cell death in CS-induced COPD.